Atom Probe Tomography of Hydrogen in a Ferritic steel - Haley, D; Chen, Y; Bagot, P; Moody, M; Gerstl, S (University of Oxford, 2017)
.pos and .rrng files were created using IVAS 3.6.6, and can be opened with the 3Depict program (http://threedepict.sourceforge.net, or in linux repositories). .rrng files are plain text, and can be altered by hand using a text editor. CSV files can be read with e.g. plain text readers or spreadsheet software.